2006
DOI: 10.1007/s00429-006-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on sympathetic innervation of the myenteric plexus and gastrointestinal smooth muscle of Fischer 344 rats

Abstract: Loss of myenteric neurons with age is well documented, however little is known about age-related changes of the sympathetic innervation of the myenteric plexus and gastrointestinal smooth muscle. The goal of the present study, therefore, was to evaluate the influence of age on the sympathetic innervation of the myenteric plexus throughout the gastrointestinal tract. Ad libitum fed virgin male Fischer 344 rats at 3, 15-16, 24, and 27-28 months of age were sampled. Whole mounts of the stomach, small intestine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 45 publications
5
51
1
Order By: Relevance
“…Rodents appear to experience a dramatic age-related degeneration of sympathetic motor neurons innervating the myenteric plexus with advancing age, which could explain agerelated decline in colonic transit [13]. Furthermore, the same study demonstrated a significant level of cholinergic vagal afferent age-related degenerative changes.…”
Section: Extrinsic Innervationmentioning
confidence: 70%
“…Rodents appear to experience a dramatic age-related degeneration of sympathetic motor neurons innervating the myenteric plexus with advancing age, which could explain agerelated decline in colonic transit [13]. Furthermore, the same study demonstrated a significant level of cholinergic vagal afferent age-related degenerative changes.…”
Section: Extrinsic Innervationmentioning
confidence: 70%
“…The presence or absence of aging effects on the innervation and function of the stomach could be critical for the satiation process in older people. At a structural level, the aging stomach is more notable for decreasing levels of sympathetic innervation than for loss of afferent fibers (23,24). Motor responses in the stomach are likely to influence the passage of water through the gut, and consequently age associated sympathetic fiber loss could effect the accurate coding of water volume in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…The contrast between maximum thirst and baseline revealed two loci of activation in the cingulate cortex in both groups: the aMCC [Y, (12,24,26); O, (12, 18, 48); Talairach coordinates] and the pACC (BA32) [Y, (8,38,2); O, (14,36,14)] (Fig. 2).…”
Section: Figmentioning
confidence: 99%
“…In earlier reports, we have characterized neuropathies as well as neuronal and glial losses in the standard rat model of aging, the Fischer 344 rat (Phillips et al, 2004b(Phillips et al, , 2006. The neuropathies commonly consist of dystrophic or markedly swollen neurites.…”
Section: Dystrophic Swellings In Alpha-synuclein-positive Processes Imentioning
confidence: 99%